FAUNA IKAN DI SUNGAI CIMADUR, CIUJUNG DAN CIBERANGDI SEKITAR TAMAN NASIONAL GUNUNG HALIMUN, KABUPATEN LEBAK, BANTEN - Ike Rachmatika; G Wahyu Dewantoro; S Sauri (Research Center for Biology-Indonesian Institute of Sciences, 2004)
Fish fauna survey were conducted in Cimadur, Ciujung and Ciberang Rivers. From these studies six fishes species were found as additional record for fishes living in Gunung Halimun National Park and its adjacent area. This finding brings the fish species living at this park to be sixty.In this record, it includes Cypriniid fishes that attain large size: Barbodes balleroides and Osteochilus hasseltii, found in the segment of the middle of R. Ciujung (18.3 m asl).